2020
DOI: 10.1021/acsomega.0c04616
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Synthesis Methods on the High-Efficiency Removal of Cr(VI) from Aqueous Solution by Fe-Modified Magnetic Biochars

Abstract: Fe-modified biochars have been widely used in removal of Cr­(VI) from water due to the resulting modified surface functional groups and magnetization property. However, few studies have synthetically investigated modification methods and synthesis parameters on the improvement of the removal efficiency of Cr­(VI) by Fe-modified biochars. Herein, 10 types of corn straw-based magnetic biochars were produced using pre-modification and post-modification methods with various modifier ratios, and the highest heating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 46 publications
(206 reference statements)
0
4
0
Order By: Relevance
“…In Figure 2(a), we observe sharp peaks at around 577, 604, and 597 cm -1 together with peaks at 615, 627, and 631 cm -1 for WHB-Co1M, WHB-Co1.5 M, and WHB-Co2M, respectively. Those mentioned spectrums are associated with the (Co 3+ )-O (in an octahedral hole) and the (Co 2+ )-O (in a tetrahedral hole) vibration [28, 29].…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 2(a), we observe sharp peaks at around 577, 604, and 597 cm -1 together with peaks at 615, 627, and 631 cm -1 for WHB-Co1M, WHB-Co1.5 M, and WHB-Co2M, respectively. Those mentioned spectrums are associated with the (Co 3+ )-O (in an octahedral hole) and the (Co 2+ )-O (in a tetrahedral hole) vibration [28, 29].…”
Section: Resultsmentioning
confidence: 99%
“…After MTP and RGD modification, the surface charge of was neutralized to −18.9 mV (MTP/RGD-CAL/TAN NS). Talk about ligands modification, there are two patterns: pre- and post-modification (Jian et al, 2020 ). Peeters et al argued that post-modified lipoplexes are better vehicles compared with pre-modified carriers (Peeters et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption mechanism varies among different biocarbon materials,particularly modified materials.Lesaoana et al (Lesaoana et al, 2019) impregnated Hawaiian activated carbon with varying concentrations of sulfuric,nitric,and phosphoric acids (20-60% v/v) and subjected it to heat in a muffle furnace.This was done to enhance the structural properties of the adsorbent and improve the removal of Cr(VI).Functional groups such as CN,NO,sulphur and phosphorus were introduced during this process and Fourier transform infrared spectroscopy showed the presence of CN,NO,sulphur and phosphorus peaks at 1213,1531,1204 and 1214 cm -1 ,respectively,demonstrating that the acid treatment resulted in the effective attachment of functional groups.The surface area of raw biochar increased from 545 m 2 /g to 824 m 2 /g after acid treatment.The optimum adsorption performance for Cr(VI) after 120 min of contact reaction was 98% at pH 1 and 93% at pH 4.Compared to raw carbon (22.3 mg/g),the adsorption capacity was increased to 40.99 mg/g with 220% (v/v) HNO 3 activator and decreased to 9.66 mg/g with 20% (v/v) H 2 SO 4 activator.Jian et al (Jian et al, 2020) found that the mechanism of adsorption of phosphate ions in the characterization of iron-modified biochar mainly involved electrostatic interactions,the presence of hydroxyl and carboxyl groups and protonation of iron oxide resulted in a positively charged surface,and this positive charge contributed to the electrostatic attraction of negatively charged PO carbon nanotubes as a novel adsorbent for the recovery of phosphate from wastewater,and the maximum experimental adsorption up to 198 mg P/g.Magnesium modified biochar presents a positively charged surface in solution due to the protonation of magnesium oxide.This positive charge produces a strong affinity for negative ions,leading to PO 4 3ion adsorption,and the adsorbed phosphate ions form Mg 3 (PO 4 ) 2 precipitation,which is the main adsorption mechanism of magnesium-modified biochar.Deng et al (Deng et al, 2021)prepared a calcium-modified chitosan microsphere for adsorption of phosphate from simulated wastewater by in situ precipitation method.The results showed that the main adsorption mechanism was coprecipitation,where PO 4 3ions were adsorbed by Ca 2+ on Ca-modified biochar,leading to the formation of the product hydroxyapatite.Luo et al (Luo et al, 2024) synthesised lanthanum-modified natural zeolite for adsorption of phosphorus by precipitation and hydrothermal methods,and the results showed that this adsorbent had an adsorption capacity of 122.7 mg/g,with good phosphorus adsorption and passivation capacity,exceeding most lanthanum-modified materials.Characterisation showed that intrasphere complexation and electrostatic attraction were the main mechanisms promoting phosphate adsorption. Typically,the removal of pollutants involves the simultaneous operation of multiple mechanisms.Various processes,such as electrostatic attraction,ion exchange,surface complexation,ligand exchange,hydrogen bonding,physical adsorption,and chemisorption,may collaboratively contribute to the overall effectiveness of pollutant removal.…”
Section: Adsorption Mechanismmentioning
confidence: 99%